Superconductivity due to Condensation of Monopoles around RCD Strings in SU(2) Gauge Theory - B. S. Rajput; Sandeep Kumar (Advances in High Energy Physics)
The study of the condensation of monopoles and the resulting chromomagnetic superconductivity have been undertaken in restricted chromodynamics of SU(2) gauge theory. Constructing the RCD Lagrangian and the partition function for monopoles in terms of string action and the action of the current around the strings, the monopole current in RCD chromo magnetic superconductor has been derived and it has shown that in London' limit the penetration length governs the monopole density around RCD string in chromo magnetic superconductors while with finite (nonzero) coherence length the leading behavior of the monopole density at large distances from the string is controlled by the coherence length and not by the penetration length.